Comparison of fidaxomicin, thuricin CD, vancomycin and nisin highlights the narrow spectrum nature of thuricin CD - L. Walsh; A. Lavelle; PM O’Connor; C. Hill; R. P. Ross (Gut Microbes, 2024)
ABSTRACTVancomycin and metronidazole are commonly used treatments for Clostridioides difficile infection (CDI). However, these antibiotics have been associated with high levels of relapse in patients. Fidaxomicin is a new treatment for CDI that is described as a narrow spectrum antibiotic that is minimally active on the commensal bacteria of the gut microbiome. The aim of this study was to compare the effect of fidaxomicin on the human gut microbiome with a number of narrow (thuricin CD) and broad spectrum (vancomycin and nisin) antimicrobials. The spectrum of activity of each antimicrobial was tested against 47 bacterial strains by well-diffusion assay. Minimum inhibitory concentrations (MICs) were calculated against a select number of these strains. Further, a pooled fecal slurry of 6 donors was prepared and incubated for 24 h with 100 µM of each antimicrobial in a mini-fermentation system together with a no-treatment control. Fidaxomicin, vancomycin, and nisin were active against most gram positive bacteria tested in vitro, although fidaxomicin and vancomycin produced larger zones of inhibition compared to nisin. In contrast, the antimicrobial activity of thuricin CD was specific to C. difficile and some Bacillus spp. The MICs showed similar results. Thuricin CD exhibited low MICs (<3.1 µg/mL) for C. difficile and Bacillus firmus, whereas fidaxomicin, vancomycin, and nisin demonstrated lower MICs for all other strains tested when compared to thuricin CD. The narrow spectrum of thuricin CD was also observed in the gut model system. We conclude that the spectrum of activity of fidaxomicin is comparable to that of the broad-spectrum antibiotic vancomycin in vitro and the broad spectrum bacteriocin nisin in a complex community.